2022
DOI: 10.1111/nph.18649
|View full text |Cite
|
Sign up to set email alerts
|

Estimating intraseasonal intrinsic water‐use efficiency from high‐resolution tree‐ring δ13C data in boreal Scots pine forests

Abstract: All material supplied via Jukuri is protected by copyright and other intellectual property rights. Duplication or sale, in electronic or print form, of any part of the repository collections is prohibited. Making electronic or print copies of the material is permitted only for your own personal use or for educational purposes. For other purposes, this article may be used in accordance with the publisher's terms. There may be differences between this version and the publisher's version. You are advised to cite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…Hence, we propose/confirm, as hypothesized in Monson et al (2018) and indicated in Tang et al (2023), that it may not be necessary to discard the EW section of δ 13 C chronologies for tree physiological and paleoenvironmental studies, when studying conifers, such as Pinus (this study) and Larix (Rinne, Saurer, Kirdyanov, Loader, et al, 2015), in boreal forests under non‐stressed to mildly stressed conditions. Apart from providing valuable information about the processes occurring during the early part of the growing season, this outcome would also give further confidence for the interpretation of δ 13 C chronologies constructed using the whole annual ring, for example, because of the presence of too narrow LW sections for manual dissection (Vitali et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Hence, we propose/confirm, as hypothesized in Monson et al (2018) and indicated in Tang et al (2023), that it may not be necessary to discard the EW section of δ 13 C chronologies for tree physiological and paleoenvironmental studies, when studying conifers, such as Pinus (this study) and Larix (Rinne, Saurer, Kirdyanov, Loader, et al, 2015), in boreal forests under non‐stressed to mildly stressed conditions. Apart from providing valuable information about the processes occurring during the early part of the growing season, this outcome would also give further confidence for the interpretation of δ 13 C chronologies constructed using the whole annual ring, for example, because of the presence of too narrow LW sections for manual dissection (Vitali et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Further, it is important to determine how this isotopic offset may vary between sites and species. The two other publications that have combined CSIA of leaf photosynthates with δ 13 C profiling of tree‐rings reported 1.0 and 0.9‰ higher values for δ 13 C Ring_ RE of mature L. gmelinii in central Siberia (Rinne, Saurer, Kirdyanov, Loader, et al, 2015) and mature P. sylvestris in southern Finland (Tang et al, 2023), respectively. There are several factors to consider, when evaluating such offsets in δ 13 C between studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Trees C5 and H2 were excluded from the analysis due to broken increment cores that did not allow ring width analysis. For δ 13 C, the analysis of 5 trees was considered adequate for the representative reconstruction of environmental variability from tree rings (Leavitt and Long, 1984;Robertson et al, 1997;Tang et al, 2022). The diameter of the trees varied between 7.9 cm and 15 cm, while the height varied between 6.6 m and 12.3 m (Table 1).…”
Section: Sampling Of Tree Coresmentioning
confidence: 99%